2019
DOI: 10.1002/cptc.201800217
|View full text |Cite
|
Sign up to set email alerts
|

A Charge‐Transfer Complex of Thioxanthonephenacyl Sulfonium Salt as a Visible‐Light Photoinitiator for Free Radical and Cationic Polymerizations

Abstract: A new double chromophoric sulfonium salt photoinitiator possessing both thioxanthone and phenacyl groups, namely 2isopropylthioxanthonium phenacyl hexafluoroantimonate (ITX-PhenS), was synthesized and characterized. ITXPhenS can form a charge-transfer complex (CTC) with the donor N,N-dimethyl aniline (DMA) with absorption characteristics in the visible range as confirmed by spectral analysis, cyclic voltammetry (CV) and density functional theory (DFT). The extension of the absorb-ance shift can be controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…The final photoreaction proposed is not to occur through classical dye/quencher interaction: as recently published, NPG can act as an electron donor to for, a CTC with iodonium acceptor . CTCs have been reported as photoinitiators of several resins . The experimental data of Figure S1 validate such an interaction.…”
Section: Resultssupporting
confidence: 62%
“…The final photoreaction proposed is not to occur through classical dye/quencher interaction: as recently published, NPG can act as an electron donor to for, a CTC with iodonium acceptor . CTCs have been reported as photoinitiators of several resins . The experimental data of Figure S1 validate such an interaction.…”
Section: Resultssupporting
confidence: 62%
“…Several photoinitiator systems based on charge transfer complex have also been reported in the cationic polymerization of epoxides [ 99 , 100 , 101 , 102 ]. In one study, Garra et al [ 103 ] reported a charge transfer complex (CTC) based on mixture of N -phenylglycine and iodonium salt (NPG-Iod) CTC that proved to be an efficient photoinitiating system in cationic polymerization of bis-cycloaliphatic epoxy monomer, enabling a curing under LED irradiation with a wavelength of 405 nm.…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
“…Recently applied CTCs based on phosphine, aniline, pyrrole, and indole acceptors were exploited as photo/thermal dual initiators but without systematic study . Some amine/Iodonium salt CTCs were also reported to initiate cationic polymerization .…”
Section: Introductionmentioning
confidence: 53%
“…9,26 Recently applied CTCs based on phosphine, aniline, pyrrole, and indole acceptors were exploited as photo/thermal dual initiators but without systematic study. [24][25][26][27][28] Some amine/ Iodonium salt CTCs were also reported to initiate cationic polymerization. 13 In this article, a series of amines will be systematically investigated to find out the impacts of the amine structure on the CTCs' initiation performance (Scheme 1).…”
mentioning
confidence: 99%